Pengaruh Pengendalian Internal dan Kompetensi Terhadap Pencegahan Kecurangan Pengelolaan Dana Desa di Kecamatan Kumpeh Ulu Kabupaten Muaro Jambi - Mufidah Mufidah; Masnun Masnun (Ekonomis: Journal of Economics and Business, 2021)
There are challenges in implementing village funds during this pandemic because the amount of absorption of village funds is used to address the conditions for handling Covid 19. The implemention of the distribution and absorption of this budget is influenced by inhibiting factors that become challenges in the implementation of village development. Internal factors in the village government are important to prevent fraud in the absorption of village funds. Therefore, one of the objectives of this study is to analyze the effect of internal control and competence on fraud prevention in Kumpeh Ulu sub-district, Muaro Jambi district. This research is causality research design. Causality research design is a type of research that is used for the purpose of testing the influence, relationship or impact of variables, the type of cross section data used and the primary data souces. This research took place from june to august 2021. The data analysis technique used SEM-PLS. The results of this study indicate that internal control and competence have an effect on fraud prevention.